Anammox response to natural and anthropogenic impacts over the Yangtze River - Chen, Liming; Liu, Sitong; Qian Chen; Zhu, Guibing; Wu, Xuan; Wang, Jiawen; Li, Xiaofei; Hou, Lijun; Ni, Jinren (Science of the Total EnvironmentScience of the Total Environment, 2019)
Increasing attention has been paid to anaerobic ammonium oxidation (anammox) in river ecosystems due to their special role in the global nitrogen cycle from land to the ocean. This study have revealed the spatial patterns of anammox bacterial response to geographic characteristics and dam operation along the Yangtze River, using N-15 tracers and molecular analyses of microbial communities in sediment samples over a 4300 km continuum. Here we found a significant temperature-related increase in anammox bacterial abundance and alpha diversity from mountainous area in the upper, fluvial plain area in the middle and lower reach, to the river mouth. In contrast, an opposite trend in anammox contribution to N-2 production (ra) was observed down the Yangtze River due to enhanced denitrification induced by spatial heterogeneity of total organic carbon. Interestingly, the Three Gorges Dam resulted in an intensive erosion and thus a change from muddy to sandy sediments within 400 km downstream the dam, which readjusted the anammox community characterized with a decreased bacterial diversity and enhanced anammox contribution to nitrogen loss. Our study highlights the importance of natural and anthropogenic impacts on anammox bacterial community and function in a complex large river ecosystem. (c) 2019 Published by Elsevier B.V.